Troubled regions and failing states the clustering and contagion of armed conflicts - Harpviken, Kristian Berg (Comparative social research, 2010)
Is the phenomenon of state failure better understood through a focus on the regional context? To what extent may studies of regional security benefit from a focus on the capacities and vulnerabilities of the states involved? These are the questions addressed in this volume of Comparative Social Research. Substantially, this special issue operates at the intersection of the larger debates on state failure and on regional (in-) security, relating to various perspectives within each of these. State failure, manifesting itself in the inability of a state to maintain its monopoly of violence, has become a widespread phenomenon in several regions of the world. While the weakness of the institutions of the state in question is an obvious dimension of state failure, there is also an important international dimension. In many of these cases, conflicts are interwoven and violence spills across borders.